Taxonomical diversity and palaeobiogeographical affinity of belemnites from the Pliensbachian–Toarcian GSSP (Lusitanian Basin, Portugal). (30th November 2020) - Rita, Patrícia; Weis, Robert; Duarte, Luís V.; De Baets, Kenneth
Abstract: High‐resolution analysis of the late Pliensbachian – early Toarcian belemnite assemblages from the Peniche section (Lusitanian Basin) has enabled, for the first time, recognition of eight taxa of the suborder Belemnitina, previously reported from contemporaneous north‐west Tethyan and Arctic sections. The presence of Bairstowius amaliae sp. nov. in the late Pliensbachian ( emaciatum Zone) represents a novelty given that hitherto the genus Bairstowius was known only from late Sinemurian and early Pliensbachian deposits. Additionally, the replacement of Bairstowius amaliae by Catateuthis longiforma, during the latest Pliensbachian, suggests an evolutionary relationship between the two taxa. This relationship suggests a new scenario for the subsequent development of endemic Toarcian Boreal–Arctic faunas, characterized by the occurrence of Catateuthis . Comparison of the Peniche belemnite fauna with coeval faunas from the Mediterranean/Submediterranean and Euro‐Boreal domains indicates taxonomic uniformity during the late Pliensbachian and early Toarcian ( emaciatum and polymorphum Zones), in the north‐west Tethys. Despite the lack of a marked taxonomic turnover, the Pliensbachian–Toarcian boundary corresponds to a slight decrease in diversity observed not only in the Lusitanian Basin but also in coeval north‐western European basins. Ordination and cluster analyses indicate that the largest changes in belemnite diversity and palaeogeographical distribution occurred rather during the Toarcian Oceanic Anoxic Event (base of the levisoni Zone). This event is marked by the extinction of taxa, affecting more severely the Mediterranean/Submediterranean domain and resulting in a more pronounced provincial differentiation among north‐western European and Arctic belemnite faunas.